Social support and uncertainty in illness on anxiety in Acute Coronary Syndrome (ACS) patients - Liza Mareta; Indra Gilang Pamungkas; Mochamad Robby Fajar Cahya; Aliana Dewi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Acute Coronary Syndrome (ACS) remains a leading cause of morbidity and mortality, with many patients experiencing high levels of anxiety during recovery. This anxiety is often exacerbated by uncertainty in illness (one of aspects that play a key role in shaping anxiety responses among patients, particularly in life-threatening conditions such as ACS) and lifestyle changes, while limited social support further hinders optimal rehabilitation. Despite its clinical importance, research exploring the combined effects of social support and uncertainty in illness on anxiety in ACS patients is still scarce, highlighting the need for this study. Objectives: This research aimed to analyse the correlation between social support and uncertainty in ilness with anxiety in ACS patient. Methods: This study used a cross-sectional design on 73 respondents at National Heart Center Harapan Kita in May - July 2025. The study was conducted using four instruments consisting of characteristics, MSPSS, SF-MUIS, and HADS. The collected data were analyzed using the Pearson test because the data were normally distributed after the Kolmogorov-Smirnov (KS) test with the results 0.723 for social support, 0.788 for uncertainty in illness, and 0.737 for anxiety (p-value > 0.05). Results: The results of the study showed a significant relationship between social support and anxiety in ACS patients (p-value: 0.012, rpearson: -0.291). Other results showed no promising relationship between uncertainty in illness and anxiety in ACS patients (p-value: 0.481, rpearson: 0.084). Conclusions: The study found that social support significantly correlated with anxiety in ACS patients while uncertainty in illness showed no significant correlation. This research is highlighting the need for further research with larger patients, integration of Mishel's Uncertainty Theory in education, and the application of Family-Centered Care in Clinical Practice